Desire-Based Theories of Reasons and the Guise of the Good - Kael McCormack (Ergo, An Open Access Journal of Philosophy)
I propose an account of desire that reconciles two apparently conflicting intuitions about practical agency. I do so by exploring a certain intuitive datum. The intuitive datum is that often when an agent desires P she will seem to immediately and conclusively know that there is a reason to bring P about. Desire-based theories of reasons seem uniquely placed to explain this intuitive datum. On this view, desires are the source of an agent’s practical reasons. A desire for P grounds conclusive knowledge of a reason to bring P about because that desire makes it true that there is a reason to do so. However, this implies that a basic desire for P can never be in error about there being at least some reason to bring P about. We have the conflicting intuition that basic desires sometimes rationally count for nothing. The guise of the good explains this intuition about the fallibility of desires. On this view, a desire for P represents P as good in some respect. Desires and reasons are independent, so a desire might misrepresent one’s reasons. But this independence is usually taken to rule out that desires ever provide conclusive knowledge of reasons. Capturing the intuition about conclusive knowledge rules out capturing the intuition about fallibility, and vice versa. I propose an epistemological disjunctivist version of the guise of the good that reconciles fallibility with the possibility of conclusive knowledge.